Differently Expressed Circular RNAs in Lacrimal Sacs From Patients With Chronic Dacryocystitis - Li, Yue; Liu, Xueru; Zhang, Wenyue; Song, Xuefei; Zhang, Leilei; Xiao, Caiwen (Frontiers in Genetics, 2022)
This study was designed to identify differently expressed circular RNAs (circRNAs) and investigate their potential roles in lacrimal sacs from patients with chronic dacryocystitis. The lacrimal sac samples from three chronic dacryocystitis patients and three control individuals were collected for RNA sequencing after depletion of ribosomal RNA. Differently expressed messenger RNAs (mRNAs) and circRNAs were used for co-expression analysis. CircRNA-microRNA (miRNA) interaction network were also established by miRanda software. Meanwhile, functional and pathway enrichment analysis were conducted for the up- and down-regulated mRNAs in the circRNA-mRNA co-expression network. The expression levels of mRNAs and circRNAs in control and chronic dacryocystitis samples were validated by quantitative real-time reverse transcription polymerase chain reaction (qRT-PCR). Among all the 3909 circRNAs predicted from RNA sequencing data, 25 circRNAs (20 up regulated and 5 down-regulated) were differentially expressed in chronic dacryocystitis samples. Besides, 1486 differentially expressed mRNAs were identified. Of these differently expressed circRNAs and mRNAs, eight were validated by qRT-PCR, including MYH2, DSP, CD27, CCL5, FN1, has_circ_0004792, has_circ_0001062 and has_circ_0115476. Gene Ontology (GO) analysis indicated that the majority of altered mRNAs in this co-expression network were involved in immune system processes and meanwhile Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis revealed that these altered expressed mRNAs were also amplified in bacterial invasion of epithelial cells, both of which were thought to be involved in the pathogenesis of chronic dacryocystitis. In the circRNA-miRNA-mRNA interaction network, six circRNAs were found to be related to Th1 and Th2 cell differentiation, which was closely associated with the development of chronic dacryocystitis. This study identified statistically significant differences between circRNAs and mRNAs of lacrimal sac samples of chronic dacryocystitis patients and control individuals and provides novel insight into the regulatory mechanism of circRNAs, miRNAs and mRNAs in the pathogenesis of chronic dacryocystitis.